The Consequences of Increased Enforcement of Legal Minimum Wages in a Developing Country: An Evaluation of the Impact of the Campa\~na Nacional de Salarios Mínimos in Costa Rica - Thomas Gindling; Nadwa Mossaad; Juan Diego Trejos S. (Institute for the Study of Labor (IZA), 2014)
In August 2010 the Costa Rican government implemented a comprehensive program to increase compliance with legal minimum wages, the Campaign for Minimum Wages. To evaluate the impact of the Campaign, we use a regression discontinuity approach, which compares what happened to workers who before the campaign had been earning below the minimum wage to those who before the Campaign had been earning above the minimum wage. We analyze a panel data set with information on workers from before the Campaign began (July 2010) and after the Campaign had been in operation for some time (July 2011). We find evidence that the Campaign led to an increase in compliance with minimum wage laws in Costa Rica; the mean earnings of those earning less than the minimum wage in 2010 increased by approximately 10% more than the earnings of those who had been earning more than the minimum wage. The Campaign led to the largest increases in the wages of women, younger workers and less-educated workers. We find no evidence that the Campaign had a negative impact on the employment of full-time workers whose wages were increased. We find some weak evidence that the Campaign had a negative impact on the employment of part-time private sector employees. Although increased inspections were mainly targeting minimum wage violations, we also observe an increase in compliance with a broader set of labor standards and a positive spillover effect relative to other violations of labor laws.
Keywords: J3; J33; J38; O17; O53; 330; Latin America; labor code enforcement; minimum wages; employment; wages